Comamonas sp. EB172 isolated from digester treating palm oil mill effluent as potential polyhydroxyalkanoate (PHA) producer - Zakaria, Mohd Rafein; Abd. Aziz, Suraini; Ariffin, Hidayah; Abdul Rahman, Nor'aini; Phang, Lai Yee; Hassan, Mohd Ali (Academic Journals, 2008)
Eleven potential polyhydroxybutyrates (PHB) producers were successfully screened from treated palm oil waste water using acetate as sole carbon and energy sources and on nitrogen limiting media with Nile Blue A dye to screen for PHB accumulation. Orange fluorescence color, produced upon binding of the dye to polymer granules in the cell, was detected when directly exposed under ultra violet light and it was further confirmed using fluorescence microscopes. Positive isolate designated as PHB5 gave the highest PHB content of 44% (g PHB/g CDW) in shake flask experiment. The metabolic properties of the bacteria was characterized using BIOLOG program and this bacterium was identified belongs to the genus Comamonas sp. Based on the peaks detected from 1H-NMR analysis, it is clearly indicated that the polyhydroxyalkanoates (PHA) produced from the bacteria was poly-(hydrobutyrate-cohydroxyvalarate)(PHBV) when the bacterium was supplied with 10 g/L acids mixture (acetic 5 : propionic 3 : butyric 2) derived from palm oil mill effluent (POME) treatment.